Bote fé no noticiário: a construção da notícia e o imaginário no telejornal católico “Canção Nova Notícias” - Xavier, Natália Laís Almeida (2019)
Since the early 1980s, the mediatization of the Catholic Church has become a growing phenomenon in Brazil and the media has become seen as an important tool for spreading its “truth” and “ideals”. TV Canção Nova is one of the Catholic national television channels, founded in 1989 by the Catholic community with the same name. The TV schedule consists of variety shows, preaching and masses, as well as journalistic production, with daily display of news and newsletters, and interview shows and weekly documentaries. We focused on the Daily News "Canção Nova Notícias" and tried to understand how journalism is used in a Catholic Network, in the face of the phenomenon of the mediatization of religion, to bring to believers the ideas and the imaginary related to Christianity. As far as typology is concerned, this is a descriptive, bibliographic and documentary research, with analysis of news reported on “Canção Nova Notícias”, with a qualitative approach. Data analysis was carried out on the basis of content analysis and general theory of the imaginary (DURAND, 2001). In addition, to support the analysis phase, we carried out in the initial methodological phase a Bibliographic Review, with the gathering of articles addressing mediatization, the communication place in the Catholic Church, TV Canção Nova and the process of newsmaking. The study is divided into three chapters. The first one concerns the mediatization of society, religion generally speaking and the Catholic Church. Whereas in the second chapter, we reflected upon journalism as a tool for producing meaning and on the presence of the imaginary in journalism. Finally, in the third chapter, we carried out the content analysis and Durand's symbolic hermeneutics in ten news stories presented on the assessed newscast to identify how the journalistic material, and the symbolic images are used in the Catholic newscast "Canção Nova Notícias” to spread religious values and how newsmaking is influenced by these aspects. After the analyses, we identified that in the texts there are often expressions or excerpts that indicate or suggest, in some situations implicitly, how Christians should act in different situations, even when the news is not directly related to religion, and that seek to spread emotions like solidarity and hope. Regarding the imaginary, what predominate are images related to the struggle to overcome difficult situations and to the construction of harmony.